Clustering Minimum Wages By Regency/City In Central Java Using The K-Means Clustering Method - Nurrohman, Setia; Sugandha, Agus; Prabowo, Agung; Mashuri, Mashuri (Department of Matematics, Universitas Padjadjaran, 2026)
The Regency/City Minimum Wage (UMK) is an important indicator in describing the level of welfare and economic activity in a region. Central Java Province, which consists of 35 regencies/cities, has quite large variations in UMK between regions. This study aims to map the grouping of regencies/cities in Central Java based on the UMK level from 2021 to 2024. The analysis was conducted using the K-Means Clustering method with the help of Microsoft Excel and RStudio software through the stages of data standardization, the Kaiser Meyer Olkin test, determining the number of clusters using the Elbow method, and an iteration process to obtain optimal results. Based on the analysis results, it was obtained that the regencies/cities in Central Java can be divided into three clusters: cluster 1 consisting of 15 regions with a low UMK level, cluster 2 consisting of 14 regions with a medium UMK level, and cluster 3 consisting of 4 regions with a high UMK level. Most areas of Central Java are included in the low and medium UMK categories, while only a small number of regions are classified as having a high UMK. These results indicate the existence of welfare disparities between regions, so it is hoped that they can be a basis for the government in formulating policies to improve welfare and economic equality in Central Java Province. Keywords: Minimum Wage, Central Java, Disparitis, K-Means Clustering